2023
DOI: 10.30892/gtg.46103-997
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Green Tourism by International Tourists and Its Impact on Green Environmental Achievement: Petra Heritage, Jordan

Abstract: The environmental advantages of green tourism are attracting the attention of a wider range of stakeholders. The behavior of travelers toward green tourism sustainability and its impact on the accomplishment of a green environment has not been well studied empirically, particularly in Petra. In this research, we use an expanded framework of the theory of planned behavior to explore the behavioral features of foreign visitors toward the sustainability of green tourism (TPB). Descriptive analysis of the explanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The authors point to the appropriate use of national parks, while emphasizing the role of distiller management. Al Fahmawee et al (2023) found in a study that tourists' intentions to engage in sustainable ecotourism are negatively affected by subjective norms, while tourists' attitudes are positively affected by these norms (Sutiksno et al, 2024). The environmental behavior of tourists is also addressed by other authors (for example, Gao et al, 2023;Paul and Roy, 2023).…”
Section: Literature Rewiev 1 Visitors To Sustainable Destinations Wit...mentioning
confidence: 99%
“…The authors point to the appropriate use of national parks, while emphasizing the role of distiller management. Al Fahmawee et al (2023) found in a study that tourists' intentions to engage in sustainable ecotourism are negatively affected by subjective norms, while tourists' attitudes are positively affected by these norms (Sutiksno et al, 2024). The environmental behavior of tourists is also addressed by other authors (for example, Gao et al, 2023;Paul and Roy, 2023).…”
Section: Literature Rewiev 1 Visitors To Sustainable Destinations Wit...mentioning
confidence: 99%
“…AlUla has consequently grown to be one of the most significant ecotourism destinations, which prioritizes environmental preservation and provides tourists with distinctive experiences by promoting sustainable economic growth, preserving natural resources, and supporting residents [2]. Therefore, the responsible authorities in AlUla resorted to adopting strategies to develop green tourism in the city to conserve the ecosystem and preserve the well-being of local residents [3]. According to Dodds and Joppe [4], the concept of green tourism has four components including (1) environmental commitment: preserving and improving nature and the physical environment to guarantee the long-term health of the ecosystems that support life; (2) local economic vitality: to maintain economic sustainability, local economies, enterprises, and communities are supported; (3) cultural diversity: respecting and valuing cultural variety is essential to ensure the long-term survival of the host or local cultures; and (4) experiential richness: offering fulfilling and pleasurable experiences via direct and meaningful engagement with people, places, animals, and cultures.…”
Section: Introductionmentioning
confidence: 99%